Myth and memory in the Mediterranean : remembering fascism's empire - Doumanis, Nicholas, 1964- (Houndmills, Hampshire : Macmillan ; New York, N.Y. : St. Martin's Press, 1997)
This book examines the relationship between coloniser and colonised among the Italian-held Dodecanese Islands between 1912 and 1943, and is based on an oral history project conducted between 1990 and 1995. Italian power is described as having been negotiated, resisted and modified by locals, who admired many aspects of Italian rule without according the regime any legitimacy. This ethnographic history challenges standard views on Italian colonialism and Greek nationalism, and reflects on contemporary questions regarding historical memory, political culture and social identity.
Introduction - Historical Background - Italy's Aegean Possession - Popular Dissent - The Poetics of Nationalism - Colonialism and Modernity - Italian Colonialism, Italian Character - Epilogue.
Includes bibliographical references (p. 231-237) and index.
The Roger Griffin ComFas Collection
Keywords: Italians -- Greece -- Dodecanese Islands -- History -- 20th century; Fascism -- Greece -- Dodecanese Islands; World War, 1939-1945 -- Campaigns -- Greece -- Dodecanese Islands; Dodecanese Islands (Greece) -- History; Italy -- Politics and government -- 1922-1945.